THE IMPACT OF THE MILITARY APPROACH TOWARDS THE CONFLICT OF TPNPB-OPM IN THE RELATION TO THE PRINCIPLE OF PROPORTIONALITY: THE IMPACT OF THE MILITARY APPROACH TOWARDS THE CONFLICT OF TPNPB-OPM IN THE RELATION TO THE PRINCIPLE OF PROPORTIONALITY - Nava M, Madinnatu; Mushtafa, Madinnatu Nava (Fakultas Hukum Universitas Trisakti, 2025)
This research examines the impact of the military approach which is considered not to be a solution to the conflict that occurred in Nduga Regency, Papua. The increasing number of refugees is one of the impacts of the prolonged conflict that has not been resolved. Through this research, the author describes the increasing number of refugees exacerbated by the fall of victims as evidence of the lack of effectiveness of the military approach in order to resolve the TPNPB-OPM conflict in Nduga Regency, Papua. This incident is contrary to the implementation of the principle of proportionality based on international humanitarian law as stipulated in the 1949 Geneva Convention. This type of research is qualitative research. The method used is descriptive juridical analytical, namely problem identification using data sources in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The result of this research is that the military approach to the TPNPB-OPM conflict in Nduga Regency, Papua is not effective enough to stop the conflict and has an impact on the increasing number of refugees which causes more civilian casualties so that it is contrary to the principle of proportionality.